Clinical features and complications of Loeys-Dietz syndrome: A systematic review. (1st September 2022) - Gouda, Pishoy; Kay, Robert; Habib, Marina; Aziz, Amir; Aziza, Eitan; Welsh, Robert
Abstract: Introduction: Loeys-Dietz syndrome (LDS) is a connective tissue disorder that arises from mutations altering the transforming growth factor β signalling pathway. Due to the recent discovery of the underlying genetic mutations leading to LDS, the spectrum of characteristics and complications is not fully understood. Methods: Our search included five databases (Pubmed, SCOPUS, Web of Science, EMBASE and google scholar) and included variations of "Loeys-Dietz Syndrome" as search terms, using all available data until February 2021. All study types were included. Three reviewers screened 1394 abstracts, of which 418 underwent full-text review and 392 were included in the final analysis. Results: We identified 3896 reported cases of LDS with the most commonly reported features and complications being: aortic aneurysms and dissections, arterial tortuosity, high arched palate, abnormal uvula and hypertelorism. LDS Types 1 and 2 share many clinical features, LDS Type 2 appears to have a more aggressive aortic disease. LDS Type 3 demonstrated an increased prevalence of mitral valve prolapse and arthritis. LDS Type 4 and 5 demonstrated a lower prevalence of musculoskeletal and cardiovascular involvement. Amongst 222 women who underwent 522 pregnancies, 4% experienced an aortic dissection and the peripartum mortality rate was 1%. Conclusion: We observed that LDS is a multisystem connective tissue disorder that is associated with a high burden of complications, requiring a multidisciplinary approach. Ongoing attempts to better characterise these features will allow clinicians to appropriately screen and manage these complications. Highlights: Loeys-Dietz Syndrome is an autosomal dominant connective tissue disease with multi-system involvement. In a systematic review of 3896 reported cases of Loeys-Dietz syndrome the most commonly reported features and complications included: aortic aneurysms and dissections, arterial tortuosity, high arched palate, abnormal uvula and hypertelorism. In the peripartum period, the rate of aortic dissections was found to be 4% with a maternal mortality of 1%.